1986
DOI: 10.1002/pen.760260806
|View full text |Cite
|
Sign up to set email alerts
|

Tensile yield in polyethylene

Abstract: Uniaxial tension tests to the yield point were performed on polyethylene as a function of temperature from 21 to 117°C at a strain rate of 2 min−1. At 21, 45, and 69°C, measurements were also made at strain rates from 0.02 to 8 min−1. Yield energy was found to be a linear function of temperature extrapolating to zero at the melting point (140°C). The ratio of thermal to mechanical energy to produce yielding is about three times smaller than for glassy amorphous polymers. The ratio of yield stress to (initial) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
7
14
0
Order By: Relevance
“…Elastic strain can be approximately obtained by dividing Young's modulus by yield stress. 17,19 The plots of elastic strain versus the filler volume fraction of composites is shown in Figure 6. It can be seen that elastic strain of materials decreases with increasing the filler volume fraction.…”
mentioning
confidence: 99%
“…Elastic strain can be approximately obtained by dividing Young's modulus by yield stress. 17,19 The plots of elastic strain versus the filler volume fraction of composites is shown in Figure 6. It can be seen that elastic strain of materials decreases with increasing the filler volume fraction.…”
mentioning
confidence: 99%
“…16 shows a drastic drop of the plastic work density for destruction of the spherulitic structure between 0 °C and 90 °C, in the whole strain range before the yield point. Hartmann et al [108][109][110] reported a general trend of linear plastic work decrease as a function of increasing deformation temperature for various polyolefins and nylon66. This phenomenon can be ascribed to the gradual decrease of the plastic flow stress, due to increasing thermal vibrations and parallel weakening of the intermolecular interaction field [111].…”
Section: Discussionmentioning
confidence: 99%
“…The yield energy per unit volume is defined as the area under the stress curve up to the yield point or the maximum point, using Ward's definition of the yield stress [17]. The thermodynamic concept of the yield energy is reported by Hartmann et al [18] on a few polymers such as PP and polyethylene and by us on the yield energy of treated polystyrene [19]. The definition of the yield energy per unit volume was reported by Macosto and Brand [20] in a relation form as…”
Section: Methodsmentioning
confidence: 99%